Exploring the relationships among art therapy students’ burnout, practicum stress, and teacher support - Jue, Juliet; Kim, Tae-Eun (Frontiers in Psychology, 2023)
This study examines how teacher support and practicum stress affect art therapy graduate students' burnout. A total of 125 master's and doctoral students from art therapy graduate schools in Korea participated in the study. The correlation analysis results showed that burnout, practicum stress, and social support are significantly interrelated. The regression analysis results indicated that practicum stress increases burnout while social support decreases it. When we used the sub-factors of social support as independent variables, we found that professor support rather than the support of colleagues or family significantly reduced burnout. When we divided the perceived teacher support into emotional support and academic support, our analysis identified that academic support was more important than emotional support to reduce students' burnout. Lastly, we discussed the significance and implications of this study.